Study of Evolution of Multi Drug Resistance Protues spp. Isolated from Patient Suffering from UTI - Ali Jaffar Saleem (Journal of Global Pharma Technology, 2019)
Clinical isolates of proteus spp. (30 isolates) were obtained from patients suffering from UTI from Baghdad Medical City hospital during the period between 1st December/2016 till 1st April 2017. The isolates were identified by culturing on MacConkey agar and blood agar then diagnosed by performing some morphological and biochemical tests. Proteus spp distributed in this study to P.mirabilis 23(76.6%) and P.vulgaris 7 (23.3%). In this study 17/30 (56.6%) of the sample were isolates from female and 13/30 (43.3%) isolates from male. Antibiotic susceptibility test for three antibiotics was performed using disc diffusion method. The percentage of highest resistance in proteus spp. isolates reached 80% (24/30) for Ampecillin and 76.6% (23) for Piperacillin while lower reached 50% (15/30) to Imipenim. Detect the resistance rates according to the sex of the patients showed significant differences for resistance to Imp in female 33.3% (10/30) compared with 16.6% (5/30) in male and for Amp, Pip in male 33.3% (10/30), 33.3% (10/30) compared with 46.6% (14/30), 43.3% (13/30) in female respectively.